DATA MART DESIGN FOR Y CLOTHING STORE SALES - Wijaya, Angeline Carolina; Beng, Jap Tji; Arisandi, Desi; Tiatri, Sri; Dinatha, Vienchenzia Oeyta Dwitama; Nurkholiza, Rahmiyana; Sefira, Fasia Meta (INTECOMS: Journal of Information Technology and Computer Science, 2025)
The data mart design for Y Clothing store aims to integrate scattered sales data to simplify analysis and speed up business decision making. Using the Kimball Nine-Step method and ETL process, sales transaction data from 2019 to 2023 is managed in a star schema. As a result, these data marts enable faster and more accurate analysis, identifying customer purchasing patterns, sales trends and promotional effectiveness. Implementation of this data mart increased inventory management efficiency by 15% and reduced sales report generation time from hours to minutes. However, challenges such as significant resource allocation for initial implementation and a learning curve for employees slowed down the maximum benefit gain somewhat. However, overall, these data marts contribute greatly to improved business decisions and more effective sales strategies. Keywords: Data Mart, Y Clothing Store, Kimball Nine-Step Method, ETL Process, Star Schema.